Design, Synthesis and Biological Evaluation of Novel Coumarin-Based Hydroxamate Derivatives as Histone Deacetylase (Hdac) Inhibitors with Antitumor Activities - Yang, Feifei (Molecules, 2019)
A series of novel coumarin-based hydroxamate derivatives were designed and synthesized as histone deacetylase inhibitors (HDACis). Selective compounds showed a potent HDAC inhibition with nM IC(50) values, with the best compound (10e) being nearly 90 times more active than vorinostat (SAHA) against HDAC1. Compounds 10e and 11d also increased the levels of acetylated histone H3 and H4, which is consistent with their strong HDAC inhibition. In addition, 10e and 11d displayed a higher potency toward human A549 and Hela cancer cell lines compared with SAHA. Moreover, 10e and 11d significantly arrested A549 cells at the G2/M phase and enhanced apoptosis. Molecular docking studies revealed the possible mode of interaction of compounds 10e and 12a with HDAC1. Our findings suggest that these novel coumarin-based HDAC inhibitors provide a promising scaffold for the development of new potential cancer chemotherapies.